2011
DOI: 10.1111/j.1740-0929.2011.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coumestrol administration to maternal mice during pregnancy and lactation on renal Ca metabolism in neonatal mice

Abstract: The present study was conducted to clarify the effects of coumestrol administration to maternal mice during pregnancy and lactation on serum Ca and Ca metabolism in their neonatal mice. From 6.5 to 16.5 days post coitus and from 3 to 10 days after parturition, maternal mice were administered at 200 µg/kg body weight/day of coumestrol. Coumestrol administration did not affect weight gains, serum Ca and the expression of vitamin D receptor (VDR) protein in the kidney of neonatal mice, but weight gains of materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Additionally, legumes contain high levels of phytoestrogen and K, and phytoestrogen administration to maternal mice during pregnancy and lactation affected renal Ca metabolism in male neonatal mice via maternal milk (Ueda et al . ). Further study is needed to clarify the effects of high K diets on kidney function in lactating animals, because the exact mechanism of high KCl diets for preventing kidney function in maternal and neonatal mice is still unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, legumes contain high levels of phytoestrogen and K, and phytoestrogen administration to maternal mice during pregnancy and lactation affected renal Ca metabolism in male neonatal mice via maternal milk (Ueda et al . ). Further study is needed to clarify the effects of high K diets on kidney function in lactating animals, because the exact mechanism of high KCl diets for preventing kidney function in maternal and neonatal mice is still unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Coumestrol is a phytoestrogen and has various physiological effects through ERs (Morito et al 2002). Our previous studies (Kirihata et al 2008(Kirihata et al , 2011Ueda et al 2012) indicated that the administration of coumestrol at a dose of 200 mg/kg body weight for pregnant and lactating mice, which is based on less than half the recommended threshold intake for isoflavones by the Ministry of Health, Labour and Welfare of Japan (Tokyo, Japan), decreased the activity of alkaline phosphatase in maternal duodenum around parturition and affected renal Ca metabolism in male neonatal mice at 11 days post partum (dpp).…”
Section: Introductionmentioning
confidence: 99%
“…In ovariectomized rats, uterine weight (wet and dry) was increased by coumestrol which has relatively weak binding affinities for estrogen receptors as compared to estradiol (Markaverich et al, ). Moreover, coumestrol administration to mice during pregnancy and lactation increased production of immunoglobulin A that is a key factor for enhancing the fetal immune system response to microbial antigens in milk (Wang et al, ) and it influenced calcium metabolism in kidneys of neonatal mice through actions via estrogen receptor alpha (Ueda et al, ). Although coumestrol has a wide spectrum of biological activities, its influence on conceptus development has not been elucidated.…”
mentioning
confidence: 99%